ACHIEVEMENTS OF TECHNOLOGY SUBJECT IN DEVELOPED FOREIGN COUNTRIES (Innovative Technologica: Methodical Research Journal, 2023)
This article shows the activities taught in foreign countries and their achievements in the lessons of subject Technological education at school. The types of training performed in schools in Switzerland, New Zealand, England and their advantages are covered.